Flotation of sylvite from potash ore by using the Gemini surfactant as a novel flotation collector. (1st March 2019) - Huang, Zhiqiang; Cheng, Chen; Zhong, Hong; Li, Liqing; Guo, Zhizhong; Yu, Xinyang; He, Guichun; Han, Haijun; Deng, Lanqing; Fu, Weng
Highlights: A novel Gemini surfactant BOBD was introduced in potash ore flotation. BOBD exhibited superior selectivity for sylvite against halite. BOBD displayed superior flotation performances than conventional surfactant OAH. Gemini BOBD is a promising collector for cleaner production of potash fertilizer. Abstract: Potash fertilizer ensures the necessary agricultural yields to feed an increasing world population. Over 80% of the world's potash fertilizer is produced by the selective froth flotation of KCl (sylvite) from NaCl (halite). However, all the surfactants used in the potash froth flotation process are traditional monomeric surfactants contain a single similar hydrophobic group in the molecule, which leads to a low production efficiency. In this work, a novel Gemini surfactant, N, N'-bis (octadecyldimethyl)-1, 4-butane diammonium dibromide (BOBD) was prepared, and originally recommended as a collector for froth flotation separation of sylvite from halite for potash ore. The performance of BOBD was compared with the results acquired using its traditional monomeric surfactant octadecylamine hydrochloride (OAH). The bench-scale flotation results showed that BOBD had excellent collecting power for sylvite and significant selectivity against halite at natural pH. Moreover, BOBD presented stronger desalination efficiency than OAH. The results gained with the Gemini collector were better in terms of KCl recovery and NaCl content than those gained with four times higher dosages of the conventional monomeric surfactant.